Analysis of Universal Health Coverage (UHC) Achievements from Triangular Policy Analysis Aspect in Pelalawan Regency - Widuri, Rita; Marlina, Hastusi; Dewi, Oktavia; Ismainar, Hetty; Rany, Novita (International Journal of Multidisciplinary Approach Research and Science, 2024)
This research aims to analyze the achievement of Universal Health Coverage (UHC) from the perspective of the Policy Analysis Triangle by examining the interconnection of actors, content, context, and process. The study, conducted in the Pelalawan Regency from June to August 2023, employs qualitative research methods with 5 primary informants and 3 supporting informants. The findings reveal that each informant's role aligns with their respective fields, indicating sufficient budgetary allocations. However, not all patients receive counseling about JKN. Regarding content, JKN covers all promotive, preventive, curative, and rehabilitative services. Differences exist in the services provided to general patients and JKN participants, with non-cut-off services functioning well. In the context aspect, all community members are obligated to be covered by JKN, and local governments can budget for JKN financing in accordance with Presidential Regulation number 83 of 2018. Both infectious and non-communicable diseases are covered by JKN, and there is no service discrimination at the first-level health facilities. Regarding the process, the UHC planning initiated in March 2022 was implemented by October 2022. Key drivers for UHC include the integration of (Integrated Social Welfare Data ) DTKS data into JKN and continuous socialization and advocacy efforts.